The Relevance Of The Historical Financial Statements In A Case Of Changes In The General Level Of Prices - مكية , نغم; محمد , نذير (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The aim of this research is to examine the level of awareness amongst accounting professionals in Syria of the relevancy of financial statements that are prepared based on historical cost during a period of changing prices (inflation).to achieve the research objective, 150 questionnaires were distributed to accounting professionals in Syria,145 of the questionnaires were returned by respondents and 130 of them were them were valid for the purpose of the analysis. The findings indicate that the accounting professionals are aware that the historical cost principle is easy to apply and understand however it is irrelevant in case of an increase in the general level of prices. The research recommends that it is important to deal with the increasing levels of prices phenomena when preparing the financial statements as failure to do so leads to misleading financial statements. Had the firm maintained the historical cost approach in preparing its financial statements, it is recommended that the firm discloses explanatory information that reflect the impact of current prices and attach this to the statements that are prepared based on the historical cost.